Electrically conductive functionalized-GNP/epoxy based composites: From nanocomposite to multiscale glass fibre composite material. (1st August 2016) - Moriche, R.; Sánchez, M.; Jiménez-Suárez, A.; Prolongo, S.G.; Ureña, A.
Abstract: The electrical behaviour and mechanical properties of functionalized graphene nanoplatelets (GNPs) reinforced epoxy-based composites were evaluated. These properties were analysed scaling up from the nanocomposite to the multiscale composite material. The electrical conductivity of 12 wt % GNPs reinforced nanocomposites was in the order of 10 −4  S/m, in contrast to the in-plane conductivity of multiscale composite materials with the same GNPs content, which was found to be ∼10 −3  S/m. This was attributed to microstructural features that also provoke the electrical conductivity through the thickness diminish down to ∼10 −4  S/m in multiscale composites. Additionally, mechanical properties were enhanced by the dispersion of GNP in nanocomposites but experienced a reduction in glass fibre composites because of the formation of a weak interface between the GNPs filled matrix and fibres.